ANALISIS PERBANDINGAN KINERJA KEUANGAN ANTARA BANK CAMPURAN DENGAN BANK ASING - Mey Indah Safitri (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2015)
The purpose of this study was 1) to analyze financial performance in terms of CAR, NPLs, ROA, ROA, NIM on bank LDR and mixtures listed in Indonesia Stock Exchange Period 2012 - 2013. 2) Analyze financial performance in terms of CAR, NPLs, ROA, ROA, LDR and NIM on foreign banks listed in Indonesia Stock Exchange Period 2012 - 2013. 3) To analyze the differences in terms of financial performance in CAR, NPLs, ROA, ROA, LDR and NIM in joint venture banks and foreign banks listed in Indonesia Stock Exchange Period 2012 - 2013. The results were obtained conclusion: 1) the financial performance of banks in terms of the mix CAR, NPLs, ROA, ROA, and NIM in the period 2012 - 2013 shows a healthy financial performance, only the LDR who demonstrate financial performance unhealthy. 2) The financial performance of foreign banks in terms of CAR, NPLs, ROA, ROA, and NIM in the period 2012 - 2013 shows a healthy financial performance, only the LDR only showing the financial performance unhealthy. 3) The analysis showed that there was no difference in terms of financial performance in the CAR, NPLs, ROA, ROA, LDR and NIM in joint venture banks and foreign banks listed in Indonesia Stock Exchange Period 2012 - 2013. Keywords: CAR, NPL, ROA, ROA, and NIM